ORGANIC PRODUCTION IN THE REPUBLIC OF SERBIA: SITUATION ANALYSIS AND THE WAY OF DEVELOPMENT - Vesna Paraušić; Vladana Hamović; Drago Cvijanović (Ekonomika Poljoprivrede (1979), 2008)
Serbia has a huge potential for organic production (pure agriculture area, climate factors, numerous of private holdings), but in the same time there are an extremely small number of organic farm with export program. One of the ways for achieve competitive advantage in the whole agricultural sector – is organic production. Future orientation this agriculture sector implied strong and systematic support public and official sector, with the larger entrepreneurship programs and initiatives in the private sector.